„Uczymy inaczej”- teoria i praktyka w kształceniu nauczycieli wczesnej edukacji - Włoch, Stanisława (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The social, political, technological and cultural changes that take place nowadays, demand changes also in teachers’ training process; since child’s development and effects of teaching depend – to a great extent – on teachers’ knowledge and competences. Contemporary system of training early education teachers contains many gaps and does not account the changes in child’s development. Most controversial is pedagogical practice – a neglected element in teacher education. The paper presents an attempt of drawing up a model training of early education teachers. The author attempts also to answer the question: what measures should be taken in the domain of teachers’ practical training, in accordance with the European tendencies.
Keywords: change; education; pedagogical practice; student; teacher